Development of Monoclonal Antibodies Which Specifically Recognize Entamoeba histolytica in Preserved Stool Samples - Yau, Yvonne C. W. (American Society for Microbiology, 2001)
We report the generation of monoclonal antibodies against a recombinant 170-kDa subunit of the Gal or GalNAc lectin of Entamoeba histolytica that specifically recognize E. histolytica but not Entamoeba dispar in preserved stool samples. These antibodies do not cross-react with other bowel protozoa, including Entamoeba coli, Giardia lamblia, and Dientamoeba fragilis.